Advanced technique of laser Doppler imaging for the diagnostics of intensity of peripheral microcirculation changes in patients with diffused liver diseases - T. D. Gelt; A. V. Borsukov (Acta Biomedica Scientifica, 2015)
It is known that changes in patients with diffuse liver disease at the vascular level are systemic in nature. Identification of these changes may help predict disease course, the possibility of the therapy revising. 60 patients with alcoholic liver cirrhosis, steatohepatitis mixed etiology, viral hepatitis "B" and "C" were examined to evaluate the possibility of non-invasive laser Doppler imaging (LDI) offorecasting the course of various forms of diffuse liver disease. Perfusion (P) c.u; in area of thenar and hypothenar of both hands were estimated by LDI. As a provocative test was applied extended cold test. Difference between initial perfusion and after cold test (AP) was analyzed (%) afterwards. ΔP < 10% was estimated as disturbance of reversibility of tissue microcirculation functional resources, that served as the basis for unfavourable forecasting with high possibility of decompensation development (it was typical of all patients with liver cirrhosis Child - Pugh C and 50% patients with liver cirrhosis Child - Pugh В). ΔP > 10%, pointed out at conservation of microcirculation in these patient and about favourable forecasting of the disease course and lower possibility of decompensation of disease during 12 month (it was typical of all patients with liver cirrhosis Child - Pugh A, steatohepatitis, viral hepatitis and 50% patients with liver cirrhosis Child - Pugh В)